Mitochondrial DNA analyses of Donax trunculus (Mollusca: Bivalvia) population structure in the Iberian Peninsula, a bivalve with high commercial importance. Issue 5 (17th July 2018) - Fernández‐Pérez, Jenyfer; Nantón, Ana; Arias‐Pérez, Alberto; Freire, Ruth; Martínez‐Patiño, Dorotea; Méndez, Josefina
Abstract: The wedge clam, Donax trunculus (Linnaeus, 1758), is an ecologically and economically important species found in the warm waters of the Atlantic and Mediterranean areas. Donax trunculus has been suffering from a severe population decline in some wild stocks of the Iberian Peninsula, and genetic monitoring of wild populations can provide valuable information to support conservation measures and management policies. In this study, mitochondrial 16S rDNA (16S) and cytochrome b (Cytb) gene variation was examined at 18 localities across the Iberian Peninsula to test whether the patterns of genetic diversity, population structure, and demographic inferences previously deduced by using microsatellites are supported by these molecular markers. Samples ( N = 557) were collected from 18 localities of the Iberian Peninsula and attention was paid to the north‐western Atlantic area, where wild stocks have diminished greatly. Analysis of molecular variance, fixation index ( F ST ), and demographic inferences were estimated based on mitochondrial DNA. Since D. trunculus shows doubly uniparental inheritance, both types of mitochondrial DNA (F and M) were analysed. A high level of genetic diversity was detected using the haplotype diversity dataset, showing different geographic patterns. F ST values for the M type revealed significant differentiation between populations on both sides of the Almeria–Oran front, and between the locality from the Alboran Sea (FU) and localities from the Atlantic Ocean. However, the F type did not detect the differentiation of FU. This makes the M genome sequences more suitable for investigating genetic structure of D. trunculus populations. Management and recovering strategies of this important resource should consider the genetic structure observed. Several strategies for conservation and management of this commercial and ecologically important bivalve are proposed.